CRIMINAL AGAINST ASSISTANT (MEDEPLICHTIGE) IN CASES OF EMBRACTION IN OFFICE AND FRAUD (CASE STUDY OF DECISION OF CENTRAL JAKARTA STATE COURT NUMBER 1194/PID.B/2018/PN JKT.SEL) - Joelyan Joelyan (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
At present the legal subjects involved in criminal acts are not only one person but now this has been carried out jointly or by more than one person, there are those who commit crimes and there are those who act as orders to commit crimes, whether those who order them to commit crimes , participating in committing, persuading to commit or even committing the act itself and there are also those who assist in criminal acts. The research method used is normative juridical, namely library law research which is carried out by examining library materials or secondary data. The results of the research include that the form or form of participation in deelneming is participating in medeplegen and assistance (medeplichtigheid) contained in Articles 55 and Article 56 of the Criminal Code (KUHP). According to the formulation of the criminal provisions in Article 55 of the Criminal Code, it reads: (1) Punished as the perpetrators of a crime, namely: 1. Those who commit, order to commit or who participate in committing; 2. Those who, by giving gifts, promises, by abusing power or reputation, by force, by threat or by causing misunderstandings or by providing opportunities, means or information, have deliberately moved other people to commit criminal acts. concerned. (2) Regarding those mentioned last, what can be accounted for is only the actions that they have deliberately moved others to do, along with the consequences. While the criminal provisions in Article 56 of the Criminal Code according to the formulation reads: (1). Those who have knowingly provided assistance in committing the crime. (2). Those who intentionally provide opportunities, means or information to commit the crime.